육아지원기관 교사의 조직몰입에 영향을 미치는 원장의 서번트 리더십과 교사의 조직 냉소주의, 임파워먼트 간의 구조적 관계 - 예남희(Nam Hee Ye); 민하영(Ha Young Min) (Korean Journal of child studies, 2014)
The purpose of this study was to investigate the structural relationships between of kindergartens and child care centers director's servant leadership, teacher's organizational cynicism, empowerment, and organizational commitment. The subjects for this study were 760 teachers of kindergartens and child care centers located in Daegu, Kyoungbuk and Ulsan district. The data collected were analyzed by means of AMOS 19.0. The results indicated that 1) The director's servant leadership, teacher's empowerment and organizational cynicism have a direct influence on organizational commitment. 2) The director's servant leadership directly influences teacher's empowerment and organizational cynicism. 3) The director's servant leadership indirectly influences teacher's empowerment and organizational cynicism in terms of the level of organizational commitment.